HYDRODYNAMIC CALCULATION OF RADIAL BEARING IN ELECTROMAGNETIC FIELD CONSIDERING ITS DEPENDENCE ON VISCOSITY AND ELECTROCONDUCTIVITY ON TEMPERATURE - K.S. AKHVERDIEV; E.O. LAGUNOVA; M.A. MUKUTADZE (Advanced Engineering Research)
We considered movement of electroconducting greasing in a backlash of the radial bearing in the presence of electromagnetic field with the account of its dependence of viscosity and electroconductivity on temperature. We estimated influence of the parametres characterising magnetic induction and intensity of electric field on the basic performance data.